Resilience Profiles of University Students: An Analysis of Differences Based on Demographic Characteristics - Annisa Andriani; Siti Raudhoh; Marlita Andhika Rahman; Verdiantika Annisa; Nurul Hafizah; Annisa Andriani; Siti Raudhoh; Marlita Andhika Rahman; Verdiantika Annisa (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Discussion surrounding mental health continues to be a prominent issue in society. Despite increasing public awareness, cases of depression, suicide, self-harm behaviors, and substance abuse persist, including among university students. In fulfilling the role of a university student, individuals encounter various personal and academic demands. Previous studies have identified resilience as a key factor enabling students to cope with such challenges constructively. Therefore, it is important to investigate factors associated with students’ levels of resilience. This study aims to identify demographic factors associated with students’ resilience levels. This research employed a quantitative approach, utilizing independent samples t-tests and ANOVA through JASP version 0.18.1.0. Data analysis was based on resilience scores obtained from 275 university students measured using the Indonesian version of the Resilience Evaluation Scale. These scores were then examined in relation to demographic factors including gender, age, campus activity involvement, financial status, and residential status. The findings revealed significant differences in students’ resilience scores based on gender, age, campus activity involvement, and residential status. In contrast, no significant differences in resilience scores were found based on financial status. The dynamics of how each factor contributes to students' resilience are further elaborated in the discussion.